The Role of Social Media and Marketing Mix 4P in Online Marketing Strategy on the Grand Everest Housing Cluster PT. Menteng Mandiri Sejahtera - Yuriza Rahayu Irawan; Sriyono Sriyono; Hadiah Fitriyah (Dinasti Publisher, 2025)
The purpose of this research is to evaluate the role of social media and the 4P marketing mix in PT's online marketing strategy. Menteng Mandiri Sejahtera for the Grand Everest Housing Cluster. Property companies must optimize their digital marketing to increase sales and market reach as marketing digitalization continues to increase. To obtain information from various related parties, such as company owners, project managers, marketing teams, property agents, and prospective buyers, this research uses a qualitative approach involving observation, interviews, and documentation. The research results show that digital marketing techniques through social media (Facebook, Instagram, and WhatsApp) and SEO can significantly increase the visibility of housing products. In addition, the effectiveness of a marketing strategy is determined by the implementation of the 4P marketing mix—product, price, place and promotion.